Safety and Efficacy of 630-nm Red Light on Cognitive Function in Older Adults With Mild to Moderate Alzheimer’s Disease: Protocol for a Randomized Controlled Study - Huang, Nayan; Yao, Dandan; Jiang, Wenjing; Wei, Cuibai; Li, Mo; Li, Wenjie; Mu, Haiyan; Gao, Maolong; Ma, Zongjuan; Lyu, Jihui; Tong, Zhiqian (Frontiers in Aging Neuroscience, 2020)
Introduction: Studies have shown that excess formaldehyde accumulation in the brain accelerates cognitive decline in people with Alzheimer’s disease (AD). Recently, reports from our research team revealed that red light treatment (RLT) improved memory in AD mice by activating formaldehyde dehydrogenase and thus reducing formaldehyde levels. Here, we developed a medical RLT device with the aim to investigate the safety and efficacy of this device in older adults with mild to moderate AD. Methods: This will be a randomized controlled trial that will include 60 participants who will be recruited and randomly divided into an RLT group and a control group. The RLT group will receive RLT intervention 5 days a week for 30 minutes each time for 24 weeks while the control group will continue their routine treatments without RLT. All participants will undergo neuropsychological and functional assessments including the Mini Mental State Examination, the Alzheimer’s disease assessment scale-cognitive subscale (ADAS-cog), the Geriatric Depression Scale (GDS), the Neuropsychiatric Inventory (NPI) and the Barthel Index at baseline, 12 weeks and at 24 weeks. All participants will undergo functional magnetic resonance imaging scanning and blood/urine biomarkers tests at baseline and 24 weeks. The primary outcome will be the ADAS-cog score while the secondary outcomes will be the GDS and NPI scores. Adverse events will be recorded and treated when necessary. Both an intention-to-treat analysis and a per-protocol analysis will be performed to evaluate the safety and efficacy of RLT. Discussion: This protocol outlines the objectives of the study and explained the RLT device developed by the research team. The study is designed as a randomized controlled trial in order to evaluate the safety and effects of the RLT device on older adults with mild to moderate AD. This study will provide evidence for the clinical use of RLT on treatment for AD. Trial registration: ChiCTR1800020163; Pre-results.